(untitled) (Pubmet, 2022)
The Stichting IFLA Foundation Programme in partnership with IFLA, LIBER, and SPARC Europe are implementing a three-year Arcadia Foundation-funded programme to reform copyright laws and regulations that enable libraries to significantly improve access to and use of copyrighted works. Knowledge Rights 21 aims to promote change at European, national, and local levels providing valuable examples for the rest of the world. The programme is driving reform in six key areas, including improving rights retention and open licensing policy and practice. Europe has seen a significant growth in activity to establish and advance open access (OA) policies. However, copyright has been the thorn in the side of many authors, funders, and their institutions who wish to publish OA, since publisher policies and processes are no longer fit for purpose. Today, we require the rights to publish, share, adapt, and reuse material for research, educational, or multilingual needs. Governments, funders, and institutions are responding in different ways to counteract publisher deadlock or restrictions as regards rights retention and open licensing. National policies have been set up in France, Spain, and the Netherlands, and umbrella organisations are calling for legislation like LIBER with its Draft Law for the use of publicly funded scholarly publications. Above all, publisher copyright policies often stand in the way of authors complying with today’s funder requirements. A SPARC Europe 2020 study provided insights into copyright policies of 10 large publishers and numerous smaller ones showing disparities between publishers and shining a light on the complexities that authors face when seeking the right to publish OA. Research funders such as the European Commission’s Horizon Europe programme and the cOAlition S Rights Retention Strategy require authors to retain publishing rights to enable them to share their work more broadly, open access and openly licensed. Funders are currently developing and implementing their strategies, although more funders will need to introduce policies until publishers change their rights retention policies. However, it is also up to the institution that is closest to the author to set publication policies and ensure publication rights for OA as demonstrated by the Harvard model all those years ago and now by the UK (Edinburgh) or Norway (Tromso). Others are piloting rights retention action, such as at the University of Cambridge. However, more efforts need to be undertaken by institutions to make it easier for their authors to legally publish OA. Knowledge Rights 21 intends to accelerate the uptake of rights retention and open licensing to enable researchers to share their work openly. It will do this by calling for publisher, institutional, and funder policy change and by empowering authors to refuse to cede their intellectual property. This presentation will shed light on some of the good practices learnt so far from publishers, institutions, and funders. Knowledge Rights 21 aims to encourage copyright reform in Europe and set up a strong and activecopyright network of libraries to see it through. The development of grassroot capacity across countries will raise the voice of libraries on copyright and build new alliances with researchers, knowledge advocates, and knowledge service providers to bring a long-lasting change. This presentation will outline how we are building this network and how you can take part in bringing about reform in rights retention and open licensing.